Influence of Increase in Phosphorus Supply on Agronomic, Phenological, and Physiological Performance of Two Common Bean Breeding Lines Grown in Acidic Soil under High Temperature Stress Conditions - Juan Carlos Suárez; Milan O. Urban; José Alexander Anzola; Amara Tatiana Contreras; José Iván Vanegas; Stephen E. Beebe; Idupulapati M. Rao (Plants, 2023)
Many common bean (Phaseolus vulgaris L.) plants cultivated in areas of the world with acidic soils exhibit difficulties adapting to low phosphorus (P) availability, along with aluminum (Al) toxicity, causing yield loss. The objective of this study was to evaluate the influence of an increase in P supply level on the agronomic, phenological, and physiological performance of two common bean breeding lines grown in acidic soil, with low fertility and under high temperature conditions, in a screenhouse. A randomized complete block (RCB) design was used under a factorial arrangement (five levels of P × 2 genotypes) for a total of 10 treatments with four replications. The factors considered in the experiment were: (i) five P supply levels (kg ha−1): four levels of P0, P15, P30, and P45 through the application of rock phosphate (RP), and one P level supplied through the application of organic matter (PSOM) corresponding to 25 kg P ha−1 (P25); and (ii) two advanced bean lines (BFS 10 and SEF10). Both bean lines were grown under the combined stress conditions of high temperatures (day and night maximum temperatures of 42.5 °C/31.1 °C, respectively) and acidic soil. By increasing the supply of P, a significant effect was found, indicating an increase in the growth and development of different vegetative organs, as well as physiological efficiency in photosynthesis and photosynthate remobilization, which resulted in higher grain yield in both bean lines evaluated (BFS 10 and SEF10). The adaptive responses of the two bean lines were found to be related to phenological adjustments (days to flowering and physiological maturity; stomatal development), as well as to heat dissipation strategies in the form of heat (NPQ) or unregulated energy (qN) that contributed to greater agronomic performance. We found that, to some extent, increased P supply alleviated the negative effects of high temperature on the growth and development of the reproductive organs of bean lines. Both bean lines (BFS 10 and SEF 10) showed adaptive attributes suited to the combined stress conditions of high temperature and acidic soil, and these two lines can serve as useful parents in a bean breeding program to develop multiple stress tolerant cultivars.